Laparorraphy in patients with colorectal cancer. Enrique Cabrera Hospital, 2019-2021 - Yusniel Lugo Echevarria; Anaisa León Mursuli; Pedro Rolando López Rodríguez (Medisur)
Foundation: an ideal technique has not been established yet to allow laparotomic closure to guarantee the reduction of complications. Objective: to compare the results of abdominal wall closure using internal subtotal points and total points in patients operated on for colorectal cancer. Methods: a descriptive, prospective and cross-sectional study was carried out at the Dr. Enrique Cabrera General Teaching Hospital, from 2019 to 2021, with 80 patients operated on for colorectal cancer. The Chi-square test, Fisher's exact test and the Mann-Whitney U test, among others, were used. Results: the tumor was located in the sigmoid colon in 35% of patients with total suture closure; and in 31.7% of the group with closure by subtotal points. Surgery was urgent in 80% of the group with total stitch closure; and elective in 75% of the closing cases with subtotal points. The incision was median supra and infraumbilical in 70% of the patients in the group with total suture closure; and xiphopubic in 66.7% of those at closure with subtotal points. There were medians of 3 ± 2 and 1 ± 0 complications for closure with total stitches and closure with subtotal stitches, respectively. Median hospital stay was longer in the total stitch closure group (8 ± 6 days). Conclusions: in the patients where internal subtotal sutures were applied for abdominal wall closure, the results were better than in the group where total sutures were used.